Correlation between muscle mass reduction and serum uric acid and urinary albumin in middle-aged and elderly type 2 diabetes men - Lin Li; Xiuli Cao; Qihong Yang (Journal of Men's Health, 2023)
This cross-sectional study correlated the muscle mass reduction with serum uric acid and urinary albumin in middle-aged and elderly men having type 2 diabetes. The study subjects were 288 middle-aged and elderly male patients with type 2 diabetes (T2DM) admitted to our hospital. They were divided into sarcopenia (n = 95) and non-sarcopenia (n = 193) groups based on whether diagnosed with sarcopenia or not. The relevant clinical information of patients was collected. Single factor analysis and multiple factor regression analysis were employed to explore the influencing factors of sarcopenia. A binary logistic regression analysis model was established for the sarcopenia probability in middle-aged and elderly men with T2DM. Hosmer and Lemeshow test evaluated the Goodness of fit of probability model. ROC (Receiver Operating Characteristic) curve was drawn by SPSS and the predictive value of prediction model was evaluated. The univariate analysis depicted that the patients in sarcopenia group compared to those in non-sarcopenia were older with lower BMI (Body Mass Index), lower UA (Uric Acid) and higher CRP (C-reactive Protein). The differences were statistically significant (p < 0.05). The binary logistic regression analysis exhibited that the age and UACR (Urine Albumin-to-Creatinine Ratio) were the risk factors, while BMI and UA were the protective factors for sarcopenia in middle-aged and elderly men with T2DM. For middle-aged and elderly male patients with T2DM, age and UACR were the risk factors, and BMI and UA were the protective factors for sarcopenia. The changes in above-stated indicators of patients with T2DM should be clinically monitored, and early and active intervention be given to high-risk groups for minimizing the sarcopenia occurrence.